Novel triphenylamine containing poly-viologen for voltage-tunable multi-color electrochromic device. (June 2021) - Kim, Keon-Woo; Lee, Jae Kyeong; Tang, Xiaowu; Lee, Yujeong; Yeo, Jihyeon; Moon, Hong Chul; Lee, Seung Woo; Kim, Se Hyun
Abstract: Electrochromic (EC) materials have been studied widely for various applications, such as smart windows, information displays, and functional energy storage devices. Among them, EC polymers are attractive materials because of their solution-processability and potential color tuning by tailoring redox-active substituents. A new EC polymer containing redox-active triphenylamine and viologen (denoted TPA-poly(viologen)) was synthesized and applied to electrochromic devices (ECDs). The resulting ECDs exhibited three different colors (magenta, blue, and orange) according to the applied voltage. For example, in the bleached state, the magenta color changed to a blue color at −1.1 V and an orange color at −1.4 V. In addition, voltage-tunable multicolor EC displays with various shapes were fabricated by electro-force-assisted dispensing (EFAD) printing. Graphical abstract: Image 1 Highlights: A new electrochromic polymer based on triphenylamine and viologen (TPA-poly(viologen)) was successfully synthesized. The electrochromic devices (ECDs) based on TPA-poly(viologen) showed three different colors (magenta, blue, and orange). A voltage-tunable multi-color EC display was fabricated by printing TPA-poly(viologen).